Effect of medium-chain fatty acid supplementation on feed intake, rumen fermentation, blood profile, and milk production of dairy cows in the transition period - K. Nishimura; H. Hirabayashi; K. Kawashima; T. Okimura; A. Suzuki; S. Asakuma; N. Isobe; T. Obitsu; S. Kushibiki; T. Sugino (Journal of Dairy Science)
ABSTRACT: Medium-chain fatty acids (MCFA) are rapidly utilized by the liver as an energy source. However, the effects of feeding MCFA to dairy cows during the transition period and the subsequent effect on postpartum performance is not clear. Therefore, the objective of this study was to evaluate the effects of MCFA supplementation on feed intake, rumen fermentation, blood profile, and milk production in dairy cows during their transition period. Twenty-one multiparity Holstein cows were randomly assigned to 2 dietary groups: one group received a diet supplemented with MCFA calcium salts (MCFA-Ca) from 3 wk relative to expected parturition to 5 wk postpartum (MCFA; n = 10), and the other group received the same diet without supplements (control; n = 11). Medium-chain fatty acid calcium salts containing 80% caprylic acid and 20% capric acid were added to the mixed diet at 1.5% DM. During the close-up period (from 3 wk relative to expected parturition until parturition), cows were fed a TMR with restricted intake to provide 100% of the metabolic energy requirement. Subsequently, the cows were fed a TMR ad libitum from parturition to 5 wk postpartum. Dry matter intake and BW did not differ throughout the experimental period between groups. Rumen fermentation and protozoa counts remained unaffected during the experimental period. Supplementation of MCFA had no effect on the plasma concentrations of nonesterified fatty acids and total ketone bodies in cows throughout the experimental period. Conversely, postpartum plasma glucagon concentration was higher in the MCFA group than in the control group, and milk yield tended to increase in the MCFA group. In conclusion, our results suggested that MCFA-Ca supplementation enhances the catabolic state by affecting pancreatic hormone secretion, resulting in an increase in milk yield during the fresh period without an excessive negative energy balance in dairy cows.